The Professional Challenges Face by the Working Journalists of Jaffna - Raguram, S.; Thuvaragan, S. (International Research Symposium 2017, Uwa Wellassa University, 2017)
During the war period in Sri Lanka, in Jaffna peninsula the media suffered lot of pressure and the utmost challenge the journalists faced was the life threat. And no other professional challenges were considered central. Now that threat is low, but, the journalists are facing other vital challenges and troubles related to their field, particularly to develop their career graph and professionalism to make them achieve the expected standards. This research on ‘The Professional Challenges Face by the Working Journalists of Jaffna’ was carried out among the working journalists full-time attached to the daily newspapers published in Jaffna; Yarl Thinakkural, Uthayan, Valampuri, and regional edition of Virakesari. This research focuses on the current Problems and challenges faced by the journalists, such as, job satisfaction, salary, training and capacity building, working hours, promotion, gender differences, right to work independently, work security, social status, psychological aspects and, the expectations of the family members. The qualitative and quantitative methodologies were employed for the research. The data for this research were collected through the survey by interviews from the chief editors and news editors and the data collected from the sub editors and staff reporters through questionnaires. The data collected were analyzed and it has been found out that the major challenges the full-time journalists of Jaffna face are regarding their wages and psychological issues and these issues cause other professional related challenges they meet. Much of the journalists are satisfied about their work and its pattern and they felt that their personal aspiration leads to choose the job even though the hardships surround them in terms of personal security in past. Contradict to the expressions of the journalists, the family members not agreed to their stand to continue the job lifelong and the family preferred to move them for the better payment avenues.
Keywords: Working Journalists; Professional Challenges; Career Development; Job Satisfaction